Participation of Arachidonic Acid Metabolism in the Aortic Aneurysm Formation in Patients with Marfan Syndrome - Soto, María E.; Guarner-Lans, Verónica; Herrera-Morales, Karla Y.; Pérez-Torres, Israel (Frontiers in Physiology, 2018)
Marfan syndrome (MFS) is a pleiotropic genetic disease involving the cardiovascular system where a fibrillin-1 mutation is present. This mutation is associated with accelerated activation of transforming growth factor β (TGFβ1) which contributes to the formation of aneurysms in the root of the aorta. There is an imbalance in the synthesis of thromboxane A2 (TXA2) and prostacyclin, that is a consequence of a differential protein expression of the isoforms of cyclooxygenases (COXs), suggesting an alteration of arachidonic acid (AA) metabolism. The aim of this study was to analyze the participation of AA metabolism associated with inflammatory factors in the dilation and dissection of the aortic aneurysm in patients with MFS. A decrease in AA (p=0.02), an increase in oleic acid (OA), TGFβ1, tumor necrosis factor alpha (TNFα), prostaglandin E2 (PGE2)(p<0.05), and COXs activity (p=0.002) was found. The expressions of phospholipase A2 (PLA2), cytochrome P450 (CYP450 4A), 5-lipoxygenase (5-LOX), COX2 and TXA2R (p<0.05) showed a significant increase in the aortic aneurysm of patients with MFS compared to control subjects. COX1, 6-keto-prostaglandin 1 alpha (6-keto-PG1α) and 8-isoprostane did not show significant changes. Histological examination of the aortas showed an increase of cystic necrosis, elastic fibers and collagen in MFS. The results suggest that there are inflammatory factors coupled to genetic factors that predispose to aortic endothelial dysfunction in the aortic tissue of patients with MFS. There is a decrease in the percentage of AA, associated with an increase of PLA2, COX2/TXA2R, CYP450 4A and 5-LOX which leads to a greater synthesis of PGE2 than of 6-keto-PGF1α, thus contributing to the formation of the aortic aneurysm. The evident loss of the homeostasis in these mechanisms confirms that there is a participation of the AA pathway in the aneurysm progression in MFS.